Societal Impact as ‘Rituals of Verification' and The Co-Production of Knowledge - Crawford, Adam (The British journal of criminology, 2020)
Thinking about and operationalizing societal impacts have become defining characteristics of university-based research, especially in the United Kingdom. This paper reflects on this unfolding shift in the conceptualization and practice of research with particular regard to criminology. It traces the development of new regulatory regimes that seek to measure research performance and render impact auditable. It argues that these ‘rituals of verification' engender instrumental and narrow interpretations of impact that accord less space to research-informed social change as a non-linear and uncertain endeavour. This is juxtaposed with a conception of societal impact rooted in methodologies of co-production. Insights from the UK Research Excellence Framework 2014 and 2021 inform discussions and are contrasted with collaborative research efforts to apply co-production in policing research.